Role of a campesine reserve zone in the Magdalena Valley (Colombia) in the conservation of endangered tropical rainforests - Trujillo-Arias, Natalia; Serrano-Cardozo, Víctor H.; Ramírez-Pinilla, Martha P. (Nature Conservation Research: Заповедная наука, 2023)
Tropical forests of Colombia have one of the highest deforestation rates in the world. The humid forest of the Magdalena valley region is one of the ecosystems with the highest risk of landscape transformation, despite being home to many endemic and threatened species. The aim of this study was to evaluate the role of a Peasant Reserve Zone in the conservation of tropical humid forests and endangered species in the Magdalena valley region. To reach this aim, we performed a multi-temporal analysis of the forest dynamics in the Peasant Reserve Zone-Cimitarra River Valley (PRZ-CRV) and assessed the extinction risk of eight species endemic to Colombia. Our outcomes indicated that the most extended land cover in the PRZ-CRV is the forest (56.30%), followed by open areas (38.75%). The forest dynamics analysis indicated that the forest cover has decreased by 3.82% between 2017 and 2019, being the area with redoubts from the Serranía de San Lucas Forest the most conserved. Finally, our results indicated that less than 50% of the climatically suitable areas for each species are covered by forests and that less than 10% of those areas are covered by Protected Areas, while for such species as Agalychnis terranova and Ateles hybridus the PRZ-CRV covered a higher percentage of their distribution than all Protected Areas together in this ecosystem. In conclusion, our results have indicated that the PRZ-CRV could be an important area for the maintenance and conservation of humid forests and their associated fauna, playing an important role as an ally to the Protected Area system in the Magdalena valley region.